2007
DOI: 10.1080/10508420701378081
|View full text |Cite
|
Sign up to set email alerts
|

How Psychotherapists Address Hypothetical Multiple Relationships Dilemmas with Asian American Clients: A National Survey

Abstract: LITTLEFORDThis study examined how psychotherapists address hypothetical nonsexual multiple relationships dilemmas with Asian American clients and identified predictors of conservative decisions and the use of culture-based rationales. This survey of 787 Asian American and non-Asian American psychotherapists revealed that clinicians rely on mostly their personal policies and seldom focus on the clients' cultural backgrounds. Psychotherapists who consider their clients' Asian culture have more cultural knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…There also have been models or guidelines developed for serving clients within specifi c contexts, such as (a) religious communities (e.g., Hill & Mamalakis, 2001 ), (b) managed care (e.g., Belar, 2000 ;Tjelveit, 2000 ;Younggren, 2000 ), (c) child clinical psychology (e.g., Mannheim et al, 2002 ), (d) outpatient care ( Truscott, Evans, & Mansell, 1995 ), and (e) play therapy ( Seymour & Rubin, 2006 ). And there are recommendations for psychologists who counsel specifi c populations of clients, such as Asian Americans (e.g., Littleford, 2007 ) or those vulnerable to exploitive dual relationships ( Gottlieb, 1993 ). These are just a few of any number of publications that address specifi c ethical challenges in mental health practice.…”
Section: A Brief Summary Of Models Applied To Specific Ethical Dilemm...mentioning
confidence: 99%
“…There also have been models or guidelines developed for serving clients within specifi c contexts, such as (a) religious communities (e.g., Hill & Mamalakis, 2001 ), (b) managed care (e.g., Belar, 2000 ;Tjelveit, 2000 ;Younggren, 2000 ), (c) child clinical psychology (e.g., Mannheim et al, 2002 ), (d) outpatient care ( Truscott, Evans, & Mansell, 1995 ), and (e) play therapy ( Seymour & Rubin, 2006 ). And there are recommendations for psychologists who counsel specifi c populations of clients, such as Asian Americans (e.g., Littleford, 2007 ) or those vulnerable to exploitive dual relationships ( Gottlieb, 1993 ). These are just a few of any number of publications that address specifi c ethical challenges in mental health practice.…”
Section: A Brief Summary Of Models Applied To Specific Ethical Dilemm...mentioning
confidence: 99%
“…The current extant literature focuses mainly on the experiences of White clinicians working with Asian American clients. For example, when examining psychotherapists’ hypothetical reactions to nonsexual multiple relationship dilemmas with their Asian American clients, Littleford (2007) observed that the majority-White survey population would rely more on their personal policies than their clients’ cultural values and backgrounds. The ones who did emphasize their clients’ cultural backgrounds were often more culturally knowledgeable, had more clinical experience, female, or Asian American themselves.…”
Section: Discussionmentioning
confidence: 99%